Virtual education environments and web mining - Sevindik, Tuncay; Demirkeser, Necmi; Comert, Zafer (Elsevier Science Bv, 2010)
Nowadays, education environments have two forms. These are traditional and virtual education environments. In both environments, one of the important problems is habit analysis and evaluation. In traditional education systems, habit analysis is done easily through observation techniques, whereas in virtual ones analyzing students' attitudes and habits is a significant problem. Web mining applications, used in providing meaningful information from meaningless habits and surfing in web environments, is the way to overcome this problem. In this study, web mining applications in virtual education environments were formed in accordance with descriptive research method. In conclusion, how web mining is used in education environments was discovered. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Attitude; distance education; education; web mining; virtual